INTERAKSI EDUKATIF MENURUT PEMIKIRAN AL-GHAZALI - Harizal Anhar (Universitas Islam Negeri Ar-Raniry, 2013)
Education is an interaction activity between teachers and students in a classroom learning. Harmonious interaction between teachers and students greatly affect the success of learning. But in reality, the issue of today's educational interaction is less attention of the education stakeholder. The evidence is that some educators develop bad relationship with the students as being arrogant and violent means in resolving problems in the classroom. These conditions depreciate the relation between the teacher and the students in or outside the class that it is not surprising some students attack the teachers. In fact, the problem of educational interaction is not a new problem in educational world. Al-Ghazali is an Islamic education leaders who concentrated on the issue since the 5th century H. This article aims at examining a depth theory of al-Ghazali on educational interaction in a number of work related to education. This research is library research through ccontent analysis to find its relevance to the world of Islamic education at the moment. The results show that Al-Ghazali has a major contribution in developing the concept of educational interaction in Islamic education. The concept of Al-Ghazali can be reference in overcoming the problems of educational interaction nowadays through an approach which is in line with the the latest developments.